The satellite layout optimization design approach for minimizing the residual magnetic flux density of micro- and nano-satellites. (October 2019) - Chen, Xianqi; Liu, Shucai; Sheng, Tao; Zhao, Yong; Yao, Wen
Abstract: With the rapid development of space technology, more and more complex micro- and nano-satellite missions have been proposed for more sophisticated objectives such as remote sensing and space astronomy. To meet these mission requirements, the satellites need to maintain a highly precise attitude control capability. However, the satellite residual magnetic moment, as the dominant disturbance torque, greatly limits the realization of the accurate attitude determination and control system. To minimize the influence of the residual magnetic field on satellite attitude determination, in this paper, a novel satellite layout optimization design (SLOD) approach is proposed. The determination method of satellite residual magnetic field is elaborated firstly and then the corresponding SLOD model concerning complex performance constraints is established. Moreover, the improved accelerated particle swarm optimization (IAPSO) algorithm is developed to search for the optimal layout solution. Finally, the feasibility and effectiveness of the proposed methodology are validated by a numerical layout example and a simplified nano-satellite layout case. Highlights: A novel satellite layout optimization design (SLOD) approach is presented. It can almost eliminate the effect of residual magnetic intensity on magnetometer. It can improve the attitude determination precision of micro- and nano-satellites.